سياسة مدير المعهد "هداية القمرية" في تحسين جودة المدرسة السلفية الوسطي ببنجكولو - Akhiruddin Akhiruddin (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
The existence of boarding school cottage in Bengkulu quite a lot that has been decline and not developed especially boarding school nuanced salafiyah. This is mostly because it still maintains traditional learning, so it does not pay attention to the guidance of society that is expected to compete with other modern schools. But boarding school Hidayatul Qomariyah Bengkulu City still can maintain and keep growing until now. This can not be separated from the position and influence of a chaplain (Kyai) as the founder and chairman of the cottage in improving the quality of the madrasah is one of them is the establishment of a policy.The type of this research is descriptive with qualitative approach. Informants from this research is the leadership of boarding schools, teachers, and educators and others. This research was conducted at MSW Hidayatul Qomariyah Kota Bengkulu. Techniques of collecting data using interviews, observation and documentation. Data analysis using Miles and Huberman model with activity of data reduction technique, data presentation, data verification.The results of this study indicate that the policy of cottage leadership in improving the quality of madrasah salafiyah wustho, that (1) The leadership of the hut has its own policy and does not comply with the standard of quality of the madrasah, both the content standard, the process, and the educators and education personnel, (2) This policy is a tradition of downhill and added lack of experts in modern education management, (3) The policy adopted by the cottage leadership does not conform to the madrasah quality standard but, the policy was taken on the basis of a tabarukan / seeking blessing to see from the previous boarding school, (4) While other factors that according to researchers who have an influence on the development and progress of the boarding school, lies in the figure of leadership that greatly affects the progress and decline of a boarding school, Then the hallmark of the hut is still traditional and special for girls only as well as monthly activities pesantren pondok involving the community prov. Bengkulu who want to get involved